Fall armyworm strains (lepidoptera: noctuidae) in Argentina: response to different mortality factors - Virla, Eduardo Gabriel (2008)
The fall armyworm (FAW) is a polyphagous pest that causes important damage in different regions of America. There are at least two morphologically identical FAW host strains. The rice strain is associated with rice and bermudagrass, while the corn strain predominates on corn, sorghum and cotton. The purpose of this work was to identify FAW host strains in Argentina and to determine their response to different mortality factors. Bioassays were conducted by using pesticides (chlorpyriphos and cypermethrin), transgenic corn (Cry 1Ab and Cry 1F) or an indigenous Bacillus thuringiensis strain (RT 3). Strain specificity was determined by the presence of diagnostic mitochondrial markers. Mean survival time data were analyzed by using NTSYS program (SM coefficient and UPGMA). Four rice strain and eleven corn strain populations were found in Argentina. The numerical analysis clearly revealed two major clusters at a similarity level of 54%. Cluster A comprised seven FAW populations, all of these identified as corn strain, while cluster B included both rice (4) and corn (4) FAW strains Acknowledgments: PICTO-UNT 761 and PIP 6062.